Challenging questions regarding the international standards. (2nd November 2018) - Solinsky, Ryan; Kirshblum, Steven C.
Abstract : Objective/Context: To highlight questions with regards to the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) and provide historical perspectives to help SCI professionals gain fuller insights into the classification system. Methods: Frequently asked questions to the ISNCSCI were collected and a review of literature and personal communications with International Standards committee members and Chairs were undertaken. Results: Background and explanations for nine questions, detailing decision processes and challenging classification rules are presented. Conclusion: While the ISNCSCI can be challenging, this background and historical explanation may provide a greater understanding and the ability to critically analyze this classification system.